A post-treatment process for composite proton exchange membrane

Through the processes of non-ionic surfactant cleaning, hardening liquid soaking, ion exchanger and neutralizing liquid treatment, and graphene oxide coating curing treatment, the problem of post-treatment of composite proton exchange membrane affecting membrane performance is solved, and the improvement is achieved Membrane performance and the effect of extending the service life of fuel cells.

CN118546413BActive Publication Date: 2025-02-07SUZHOU KERUN NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410698066.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-02-07
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

The post-treatment process of the existing composite proton exchange membrane may reduce the ion conduction and mechanical properties of the membrane, affecting its long-term stable operation in fuel cells.

Method used

The composite proton exchange membrane was cleaned with a nonionic surfactant, followed by soaking in the hardened liquid to promote coagulation and hardening, and treated in the ion exchanger and neutralizing liquid to optimize the membrane structure. Finally, a graphene oxide coating is applied and cured.

Benefits of technology

Through this process, the performance of the composite proton exchange membrane is stabilized, its ion exchange capacity, proton conductivity and chemical stability are improved, and the membrane structure is optimized to enhance mechanical strength and dimensional stability, thereby improving the performance and service life of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118546413B_ABST
    Figure CN118546413B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of proton exchange membranes and provides a post-treatment process of a composite proton exchange membrane. The post-treatment process comprises: placing the composite proton exchange membrane in a non-ionic surfactant for cleaning, placing the composite proton exchange membrane in an ion exchange agent for waiting for 0.5 hours after drying treatment, placing the composite proton exchange membrane in a neutralizing solution for soaking for 0.5 hours, then drying treatment, finally cleaning the surface of the composite proton exchange membrane and coating it with a graphene oxide coating, and curing the surface coating of the composite proton exchange membrane after drying treatment. The present invention stabilizes the performance of the composite proton exchange membrane by using a non-ionic surfactant and thoroughly cleans the impurities remaining on the surface of the composite proton exchange membrane, ensuring that no influence is caused on the subsequent hardening treatment, and then the non-ionic surfactant remaining on the surface of the composite proton exchange membrane accelerates the coagulation and hardening of the composite proton exchange membrane, thereby improving the performance of the proton exchange membrane, such as ion exchange capacity, proton conductivity, chemical stability, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of proton exchange membranes, in particular to a post-treatment process of a composite proton exchange membrane. Background Art

[0002] Composite proton exchange membrane is a thin film material with proton conductivity, usually a composite structure composed of a proton exchange membrane matrix and a supporting material. The proton exchange membrane matrix usually uses a polymer material with proton conductivity, such as polytetrafluoroethylene (PTFE), polystyrene sulfonic acid (PSSA), etc.; while the supporting material is used to enhance the mechanical strength and stability of the membrane. Composite proton exchange membrane has important application value in fuel cells, water electrolysis hydrogen production, electrolytic sewage treatment and other fields.

[0003] Composite proton exchange membrane is an important material used in proton exchange membrane fuel cells. The main purpose of the post-treatment process is to improve the performance of the membrane and ensure its long-term stable operation in the battery. However, some treatment processes may affect the performance of the membrane, such as reducing ion conductivity and changing mechanical properties.

[0004] In summary, the present invention provides a post-treatment process for a composite proton exchange membrane to solve the above problems. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a post-treatment process of a composite proton exchange membrane to overcome the deficiencies in the prior art.

[0006] The technical solution of the present invention is as follows:

[0007] A post-treatment process for a composite proton exchange membrane comprises the following steps:

[0008] S1. The composite proton exchange membrane is placed in a nonionic surfactant for cleaning. The nonionic surfactant is used to stabilize the performance of the composite proton exchange membrane and to thoroughly clean the impurities remaining on the surface. The cleaned composite proton exchange membrane is placed in a hardening solution and soaked for 1.5 hours, and then placed in a neutralizing solution and soaked for 1 hour;

[0009] The main material of the composite proton membrane is perfluorosulfonic acid, and the hardening liquid is a mixture of 10%-30% sodium hydroxide solution and 60-80ml of pure water. The polymers in the perfluorosulfonic acid interact with each other, thereby causing it to condense and harden.

[0010] S2, drying the composite proton exchange membrane, placing it in an ion exchanger and waiting for 0.5 h, then placing it in a neutralizing solution and soaking it for 0.5 h, and then drying it;

[0011] S3, preparing a graphene oxide solvent, the preparation steps of the graphene oxide solvent: pouring 5%-10% of graphene powder into 1%-3% of an oxidant and waiting for 1h-24h, pouring graphene oxide into 1%-3% of a reducing agent and waiting for 1h-24h, and finally mixing in 80%-90% of pure water;

[0012] S4. After cleaning the surface of the composite proton exchange membrane, a graphene oxide coating is applied thereon, and after drying, the surface coating of the composite proton exchange membrane is cured, and finally a performance test is performed.

[0013] Furthermore, the neutralizing solution in S1 is a mixture of 0.25 mol hydrochloric acid solution and 60-90 ml pure water.

[0014] Furthermore, the ion exchanger in S2 is a polymer resin and chlorosulfuric acid in a ratio of 1:3, and the reaction is carried out under acidic conditions with a pH value of 6.5-7.5 during the mixing process.

[0015] Furthermore, the neutralizing solution in S2 is 0.1 m phosphate buffer.

[0016] Furthermore, the curing treatment in S4 is ultraviolet light irradiation.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. The present invention stabilizes the performance of the composite proton exchange membrane by a non-ionic surfactant and thoroughly cleans the impurities remaining on the surface thereof to ensure that it will not affect the subsequent hardening treatment. Then, the non-ionic surfactant remaining on the surface of the composite proton exchange membrane accelerates the coagulation and hardening of the composite proton exchange membrane, thereby improving the performance of the proton exchange membrane, such as ion exchange capacity, proton conductivity, chemical stability, etc.; optimizes the structure of the membrane to make it more uniform and dense, improves the mechanical strength and dimensional stability of the membrane, and does not damage the original performance of the composite proton exchange membrane during the optimization process. Through this post-treatment process, a composite proton exchange membrane with better performance can be obtained, thereby improving the performance and service life of the proton exchange membrane fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The present invention is a flow chart of a post-treatment process of a composite proton exchange membrane. DETAILED DESCRIPTION

[0020] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0021] Embodiment 1:

[0022] A post-treatment process for a composite proton exchange membrane comprises the following steps:

[0023] S1. The composite proton exchange membrane is placed in a non-ionic surfactant for cleaning, and the cleaned composite proton exchange membrane is placed in a hardening solution and soaked for 1.5 hours, wherein the hardening solution is a mixture of 10% sodium hydroxide solution and 60 ml of pure water, and then placed in a neutralizing solution and soaked for 1 hour;

[0024] S2, after drying the composite proton exchange membrane, place it in an ion exchanger and wait for 0.5h, and then place it in a neutralizing solution and soak it for 0.5h, wherein the neutralizing solution is a mixture of 0.25mol hydrochloric acid solution and 60ml pure water, and then dry it;

[0025] S3, preparing a graphene oxide solvent, the preparation steps of the graphene oxide solvent are: pouring 5% of graphene powder into 1% of an oxidant and waiting for 6 hours, pouring graphene oxide into 1% of a reducing agent and waiting for 6 hours, and finally mixing in 90% of pure water;

[0026] S4. After cleaning the surface of the composite proton exchange membrane, a graphene oxide coating is applied thereon, and after drying, the surface coating of the composite proton exchange membrane is cured, and finally a performance test is performed.

[0027] Embodiment 2:

[0028] S1. The composite proton exchange membrane is placed in a non-ionic surfactant for cleaning, and the cleaned composite proton exchange membrane is placed in a hardening solution and soaked for 1.5 hours, wherein the hardening solution is a mixture of 30% sodium hydroxide solution and 70 ml of pure water, and then placed in a neutralizing solution and soaked for 1 hour;

[0029] S2, after drying the composite proton exchange membrane, place it in an ion exchanger and wait for 0.5h, and then place it in a neutralizing solution and soak it for 0.5h, wherein the neutralizing solution is a mixture of 0.25mol hydrochloric acid solution and 80ml pure water, and then dry it;

[0030] S3, preparing a graphene oxide solvent, the preparation steps of the graphene oxide solvent are: pouring 7% of graphene powder into 2% of an oxidant and waiting for 6 hours, pouring graphene oxide into 2% of a reducing agent and waiting for 6 hours, and finally mixing in 90% of pure water;

[0031] S4. After cleaning the surface of the composite proton exchange membrane, a graphene oxide coating is applied thereon, and after drying, the surface coating of the composite proton exchange membrane is cured, and finally a performance test is performed.

[0032] Embodiment 3:

[0033] S1. The composite proton exchange membrane is placed in a non-ionic surfactant for cleaning, and the cleaned composite proton exchange membrane is placed in a hardening solution and soaked for 1.5 hours, wherein the hardening solution is a mixture of 30% sodium hydroxide solution and 60 ml of pure water, and then placed in a neutralizing solution and soaked for 1 hour;

[0034] S2, after drying the composite proton exchange membrane, place it in an ion exchanger and wait for 0.5h, and then place it in a neutralizing solution and soak it for 0.5h, wherein the neutralizing solution is a mixture of 0.25mol hydrochloric acid solution and 90ml pure water, and then dry it;

[0035] S3, preparing a graphene oxide solvent, the preparation steps of the graphene oxide solvent: pouring 10% of graphene powder into 3% of an oxidant and waiting for 6 hours, pouring graphene oxide into 3% of a reducing agent and waiting for 6 hours, and finally mixing in 90% of pure water;

[0036] S4. After cleaning the surface of the composite proton exchange membrane, a graphene oxide coating is applied thereon, and after drying, the surface coating of the composite proton exchange membrane is cured, and finally a performance test is performed.

[0037] Comparative Example:

[0038] S1. The composite proton exchange membrane is placed in an anionic surfactant for cleaning, and the cleaned composite proton exchange membrane is placed in a hardening solution for 1.5 hours, wherein the hardening solution is a mixture of 70% concentrated sulfuric acid solution and 80 ml of pure water, and then placed in a neutralization solution for 1 hour, wherein the neutralization solution is a mixture of 30% sodium hydroxide solution and 90 ml of pure water;

[0039] S2, after drying the composite proton exchange membrane, place it in an ion exchanger and wait for 0.5h, and then place it in a neutralizing solution and soak it for 0.5h, wherein the neutralizing solution is a mixture of 0.25mol hydrochloric acid solution and 90ml pure water, and then dry it;

[0040] S3, preparing a cationic polymer coating solution;

[0041] S4. After cleaning the surface of the composite proton exchange membrane, a graphene oxide coating is applied thereon, and after drying, the surface coating of the composite proton exchange membrane is cured, and finally a performance test is performed.

[0042] In Comparative Example 1 of the present invention, the nonionic surfactant in Examples 1-3 is replaced by anionic surfactant, the 10% sodium hydroxide solution is replaced by 70% concentrated sulfuric acid solution, and the graphene oxide solvent is replaced by a cationic polymer coating solution; wherein, since the material of the existing composite proton exchange membrane is perfluorosulfonic acid, and the nonionic surfactant is not easy to react when in contact with perfluorosulfonic acid, and since there is no obvious cationic or anionic feature in the molecules of the nonionic surfactant, it will not cause damage to the performance of the composite proton exchange membrane, and the nonionic surfactant has residual solvents, salts or other impurities, ensuring that the membrane surface is clean and pure;

[0043] Perfluorosulfonic acid is a relatively strong acidic compound, and concentrated sulfuric acid is an acidic substance. Therefore, when perfluorosulfonic acid comes into contact with concentrated sulfuric acid, a violent reaction may occur, causing the composite proton exchange membrane to be in an unstable state. Sodium hydroxide is an alkaline compound, so it is relatively difficult for them to react chemically. Sodium hydroxide can interact with the polymer in the composite proton exchange membrane, thereby causing it to condense and harden. This hardening process can enhance the structural stability of the membrane and improve its mechanical properties, making it more suitable for practical applications. It can also promote the functionalization reaction on the membrane surface, thereby improving the membrane's antioxidant and chemical stability. In addition, sodium hydroxide also has the function of adjusting the pH value. In the post-treatment process of the composite proton exchange membrane, a suitable pH value can promote the physical and chemical changes of the membrane, thereby further improving its performance and stability.

[0044] The coating solution containing graphene oxide can improve the conductivity and chemical corrosion resistance of the membrane; the post-treatment process first stabilizes the performance of the composite proton exchange membrane through a non-ionic surfactant and thoroughly cleans the impurities remaining on the surface to ensure that it will not affect the subsequent hardening treatment, and then coagulates and hardens it through sodium hydroxide, and the non-ionic surfactant remaining on the surface of the composite proton exchange membrane can promote the interaction between sodium hydroxide and the polymer in the composite proton exchange membrane, accelerate the coagulation and hardening of the composite proton exchange membrane, and improve the performance of the proton exchange membrane, such as ion exchange capacity, proton conductivity, chemical stability, etc.; optimize the structure of the membrane to make it more uniform and dense, improve the mechanical strength and dimensional stability of the membrane, and will not cause damage to the original performance of the composite proton exchange membrane during the optimization process. Through this post-treatment process, a composite proton exchange membrane with better performance can be obtained, thereby improving the performance and service life of the proton exchange membrane fuel cell.

[0045] The post-treatment process of a composite proton exchange membrane of Examples 1-3 and Comparative Example was tested, and the specific steps are as follows:

[0046] Thickness uniformity test: 1. The zero point of the thickness gauge should be calibrated before each measurement, and its zero point should be rechecked after each sample measurement;

[0047] 2. When measuring, lower the measuring head gently to avoid deformation of the sample. During the test, the strength applied by the measuring head on the sample surface should be between 0.7N / cm2 and 2N / cm;

[0048] 3. Test in a constant temperature and humidity environment with a temperature of 29℃±3℃ and a relative humidity of 55%±6%. There should be no less than 30 test points per 100cm sample, and they should be evenly distributed. The distance between the test points and the edge of the sample should be greater than 5mm, and each group of samples should have at least 3 test points.

[0049] Tensile test: 1. Under constant temperature and humidity conditions of 29℃±3℃ and 55%±6%, place the proton exchange membrane sample in the fixture of the intelligent electronic tensile testing machine, so that the longitudinal axis of the sample coincides with the center line of the upper and lower fixtures, and clamp it;

[0050] 2. When measuring tensile strength and elongation at break, different tensile speeds can be used, ranging from 50 mm / min to 200 mm / min. For each tensile speed, a separate specimen should be used;

[0051] 3. When measuring the elastic modulus, the test speed selected by the intelligent electronic tensile testing machine should make the strain rate close to 1% of the gauge length per minute;

[0052] The performance tests of the samples of Examples 1-3 and the comparative example were conducted three times respectively: Example 1 sample: cleaned with a non-ionic surfactant, immersed in a hardening solution of 10% sodium hydroxide solution and 60 ml of pure water, and the preparation steps of the graphene oxide solvent are 5% graphene powder poured into 1% oxidant and waited for 6 hours, and the graphene oxide was poured into 1% reducing agent and waited for 6 hours, and finally mixed with 90% pure water for coating;

[0053] Example 2 Sample: Cleaned with a nonionic surfactant, immersed in a hardening solution of 30% sodium hydroxide solution and 70 ml of pure water, and the preparation steps of the graphene oxide solvent are 7% graphene powder poured into 2% oxidant and waited for 6 hours, and the graphene oxide was poured into 2% reducing agent and waited for 6 hours, and finally mixed with 90% pure water for coating;

[0054] Example 3 Sample: Cleaned with a nonionic surfactant, immersed in a hardening solution of 30% sodium hydroxide solution and 60 ml of pure water, and the preparation steps of the graphene oxide solvent are 10% of graphene powder poured into 3% oxidant and waited for 6 hours, and the graphene oxide was poured into 3% reducing agent and waited for 6 hours, and finally mixed with 90% pure water for coating;

[0055] Comparative sample: cleaned with anionic surfactant, immersed in a hardening solution of 70% concentrated sulfuric acid solution added with 80 ml of pure water, and coated with a cationic polymer coating solution;

[0056] Experimental data:

[0057]

[0058] In the performance test of the composite proton exchange membrane of Example 1, the conductivity, tensile strength and tensile modulus are the largest, indicating that the composite proton exchange membrane processed by the post-treatment process of Example 1 has excellent performances.

[0059] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A post-treatment process for a composite proton exchange membrane, characterized in that: The steps include: S1. The composite proton exchange membrane is placed in a nonionic surfactant for cleaning. The nonionic surfactant is used to stabilize the performance of the composite proton exchange membrane and to thoroughly clean the impurities remaining on the surface. The cleaned composite proton exchange membrane is placed in a hardening solution and soaked for 1.5 hours, and then placed in a neutralizing solution and soaked for 1 hour; The main material of the composite proton membrane is perfluorosulfonic acid, and the hardening liquid is a mixture of 10%-30% sodium hydroxide solution and 60-80ml of pure water. The polymers in the perfluorosulfonic acid interact with each other, thereby causing it to condense and harden. S2, drying the composite proton exchange membrane, placing it in an ion exchanger and waiting for 0.5 h, then placing it in a neutralizing solution and soaking it for 0.5 h, and then drying it; S3, preparing a graphene oxide solvent, the preparation steps of the graphene oxide solvent: pouring 5%-10% of graphene powder into 1%-3% of an oxidant and waiting for 1h-24h, pouring graphene oxide into 1%-3% of a reducing agent and waiting for 1h-24h, and finally mixing in 80%-90% of pure water; S4. After cleaning the surface of the composite proton exchange membrane, a graphene oxide coating is applied thereon, and after drying, the surface coating of the composite proton exchange membrane is cured, and finally a performance test is performed.

2. A post-treatment process for a composite proton exchange membrane as claimed in claim 1, characterized in that: The neutralizing solution in S1 is a mixture of 0.25 mol hydrochloric acid solution and 60-90 ml pure water.

3. A post-treatment process for a composite proton exchange membrane as claimed in claim 1, characterized in that: The ion exchanger in S2 is a polymer resin and chlorosulfuric acid in a ratio of 1:3, and the reaction is carried out under acidic conditions with a pH value of 6.5-7.5 during the mixing process.

4. A post-treatment process for a composite proton exchange membrane as claimed in claim 1, characterized in that: The neutralizing solution in S2 is 0.1 M phosphate buffer.

5. A post-treatment process for a composite proton exchange membrane as claimed in claim 1, characterized in that: The curing treatment in S4 is ultraviolet light irradiation.

Citation Information

Patent Citations

  • Modification method for proton exchange membrane of all-vanadium redox flow battery

    CN106602112A

  • SPEEK / PVP / HEC proton exchange membrane and preparation method

    CN109251472A